2021
DOI: 10.1371/journal.pone.0248209
|View full text |Cite
|
Sign up to set email alerts
|

A strontium isoscape for the Conchucos region of highland Peru and its application to Andean archaeology

Abstract: Strontium isotope (87Sr/86Sr) analysis of human skeletal remains is an important method in archaeology to examine past human mobility and landscape use. 87Sr/86Sr signatures of a given location are largely determined by the underlying bedrock, and these geology specific isotope signatures are incorporated into skeletal tissue through food and water, often permitting the differentiation of local and non-local individuals in past human populations. This study presents the results of a systematic survey of modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 126 publications
2
4
0
Order By: Relevance
“…This conclusion is supported by strontium isotope analysis of teeth (n = 4) from 4 different deer recovered from the excavations at Canchas Uckro. The strontium values (Supplemental Table S7) of these deer match closely with the bioavailable strontium in the area immediately surrounding Canchas Uckro (Washburn et al 2021). Supporting evidence for the importance of hunting includes the high number of chipped stone and ground slate projectile points (n = 18) that were recovered from Canchas Uckro (Supplemental Figure S9).…”
Section: Hunting Practicessupporting
confidence: 53%
“…This conclusion is supported by strontium isotope analysis of teeth (n = 4) from 4 different deer recovered from the excavations at Canchas Uckro. The strontium values (Supplemental Table S7) of these deer match closely with the bioavailable strontium in the area immediately surrounding Canchas Uckro (Washburn et al 2021). Supporting evidence for the importance of hunting includes the high number of chipped stone and ground slate projectile points (n = 18) that were recovered from Canchas Uckro (Supplemental Figure S9).…”
Section: Hunting Practicessupporting
confidence: 53%
“…Hobson et al, 2010;Muhlfeld et al, 2012;Song et al, 2014;Chesson et al, 2018;Colleter et al, 2021;Lazzerini et al, 2021). So far, national isoscapes have been produced for several European and extra-European countries, employing and testing several different methods for the spatial interpolation, including machine learning (Montgomery et al, 2006;Evans et al, 2010;Frei and Frei, 2011;Bataille and Bowen, 2012;Pestle et al, 2013;Hartman and Richards, 2014;Copeland et al, 2016;Kootker et al, 2016;Laffoon et al, 2017;Bataille et al, 2018;Hedman et al, 2018;Willmes et al, 2018;Adams et al, 2019;Ladegaard-Pedersen et al, 2020;Scaffidi and Knudson, 2020;Snoeck et al, 2020;Wang and Tang, 2020;Frank et al, 2021;Funck et al, 2021;Washburn et al, 2021;Zieliński et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Isotopic methods on their own are limited for determining the ancestral regions from where these individuals might have originated. For example, high degrees of Sr-isotopic variability and the absence of regional and pan-regional isoscapes limit inferences ( 29 ). After reviewing all of the available evidence, Inca specialist D’Altroy ( 2 ) concluded that the people of the estate complex at Machu Picchu were largely from areas to the south of Cusco, but he hesitated to be more specific.…”
Section: Introductionmentioning
confidence: 99%